Primera producción de ajo (Allium sativum) en un sistema de acuaponía en Argentina - Alarcon, Aldo José; Guerrero, Silvana Alejandra; Casimiro Bonifacio, David Cosme; Tombari, Andrea Diana (Universidad Nacional de Río Negro, 2025)
Poster